For this case we must simplify the following expression:
[tex](1-2n) -7n (12-2) =[/tex]
We solve the operation of the second parenthesis, taking into account that different signs are subtracted and the sign of the major is placed:
[tex](1-2n) -7n (10) =[/tex]
We multiply:
[tex](1-2n) -70n =[/tex]
We eliminate the parentheses:
[tex]1-2n-70n =[/tex]
We add similar terms, taking into account that equal signs are added and the same sign is placed:
[tex]1-72n[/tex]
Answer:
The simplified expression is: [tex]1-72n[/tex]